Complete septate uterus with cervical duplication and longitudinal vaginal septum: an uncommon mullerian anomaly - Sonawane, Pundalik K.; Bhavsar, Urvi C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The most commonly reported mullerian duct anomalies are septate, arcuate, didelphys, unicornuate or hypoplastic uteri. Here we describe a presentation of unusual mullerian anomaly. We report a case of 31 year old nulliparous woman with primary infertility married since 5 years with history of excision of longitudinal vaginal septum 2 years back. Clinical examination revealed two cervix. On ultrasound, she was diagnosed with single fundus with 2 uterine cavities and double cervix with complete septum within. Diagnosis was confirmed with hysterosalpingogram and MRI showing no communication between the two uterine cavities. On combined laproscopy and hysteroscopy, the septum was excised above the level of cervix transforming into a single cavity uterus with free bilateral spillage of fallopian tubes, keeping the two cervix intact. This anomaly is inconsistent with generally accepted understanding of mullerian development but fits within alternative hypothesis. Establishing an accurate diagnosis is essential for planning treatment and management strategies.